On the existence of focal and conjugate points of half-linear second-order differential equation on a given interval - Ramazanova, Kh.S. (Bulletin of the Karaganda University. Mathematics Series, 2015)
Established conditions for the existence of focal points and conjugate points of half-linear second-order differential equations on a given interval and are given oscillatory conditions.